(untitled) (Research, Society and Development, 2021)
Knowledge about landscapes is the first step to identify the potential and limitations of the region, and, consequently, plan and properly manage natural resources. Therefore, the objective of this work was to carry out the hydrogeomorphometric characterization of the Maritaca river microbasin, to provide basic information for planning sustainable development. The hydrogeomorphometric parameters were analyzed using Google Earth, QGIS and TrackMaker Free softwares, altimetric images from the ALOS satellite and equations from the literature. The microbasin of the Maritaca river has an area of 9.83 km2, perimeter of 15.48 km, form factor of 0.20, circularity index of 0.52 (intermediate shape), compactness coefficient of 1.38 (low medium susceptibility to floods), altitude ranging from 229 to 324 m, predominance of smooth wavy (44.15%) and wavy (40.08%) reliefs, 4th order dendritic drainage pattern (high conditions for fish housing), medium density of springs, high drainage density, maintenance coefficient of 391.6 m2 m-1, sinuosity index of 26.21% (straight main channel) and concentration time of 1.69 h (low). The microbasin has potential for agricultural development, however, conservation management practices are recommended, especially in steeper areas and close to riparian zones, to mitigate possible problems related to soil and water losses, and contamination of water resources.The results obtained will help in the planning of agricultural practices and management of natural resources, enabling the sustainable development of the region.